Leveraging Technology for Targeted Student Support in Large Enrollment Chemistry Courses - Meghan Porter; Kim Arnold (Journal of Teaching and Learning with Technology)
Large enrollment courses present unique challenges in providing student support. Despite our efforts to provide various help sessions throughout the week, it is inevitable that not all students can attend, and individual meetings are not feasible. Students may hesitate to ask questions on previous topics, feeling like they will slow down their peers. To address these challenges in three large enrollment chemistry courses, we have implemented digital whiteboarding and established directed help sessions in the ALCOVE (Active Learning Classroom of Valuable Experiences) classroom. This approach enhances accessibility and provides targeted support, fostering an environment that encourages active engagement and collaboration among peers. Utilizing digital whiteboards in help sessions allows students to access content afterward, alleviating concerns about missing crucial details that may be erased. This accessibility benefits students unable to attend, providing them with a means to review discussed content without placing an additional burden on the instructor. Additionally, while students are studying, they can leave digital post-its for the instructor to address at the next session, decreasing the stress of asking questions live in front of their peers. Weekly targeted help sessions, using a OneNote notebook organized by weeks and topics, enables students to focus on specific content areas they are struggling with.